Splenic B-Cell Lymphomas with Diffuse Cyclin D1 Protein Expression and Increased Prolymphocytic Cells: A Previously Unrecognized Diagnostic Pitfall - Khaled Algashaamy; Yaohong Tan; Nicolas Mackrides; Alvaro Alencar; Jing-Hong Peng; Joseph Rosenblatt; Juan P Alderuccio; Izidore S. Lossos; Francisco Vega; Jennifer Chapman (Case Reports in Hematology)
Prolymphocytic transformation is a concept usually applied in the context of chronic lymphocytic leukemia/small lymphocytic lymphoma to describe the presence of a high percentage of prolymphocytes in peripheral blood (usually more than 55%). Prolymphocytic transformation has also been reported in mantle cell lymphoma (MCL) but only rarely in splenic marginal zone lymphoma (SMZL). We present two splenic B-cell lymphomas presenting in the leukemic phase and with increased prolymphocytes, both classified as SMZL with prolymphocytic transformation. One case clinically simulated B-prolymphocytic leukemia (B-PLL). Both lymphomas were very unusual because the tumor cells diffusely and strongly expressed cyclin D1 despite lacking the t(11; 14)(q13; q32) as detected by several approaches including next-generation sequencing, fluorescence in situ hybridization using CCND1 break apart probe and fusion probes for t(11; 14)(q13; q32), and conventional karyotyping. These cases therefore simulated prolymphocytic variants of MCL. The incidence of this phenomenon is unknown, and awareness of this potential alternate protein expression pattern is important in order to avoid diagnostic errors.